Chronic renal insufficiency and its impact on the social relations of the injured "Sociological study in Lattakia" (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current research aims to study chronic renal insufficiency as a social phenomenon that threatens the life of the human being to the extent of its danger to inevitable death. Therefore, the study included (45) cases of infection, and associated with the filter machine, They were selected from the specialized blood purification center in Lattakia. Our current research includes how scouting aims to explore and understand chronic renal insufficiency, its social significance (perception), and its impact on family and social relationships. In other words, the social effects of the disease, the status of the hospitalization from the point of view of the patients themselves, and how did the status of the hospital affect the patient's social relations?